Greater Connection Stability With Zoom Over Doxy.me in a Student-Led Free Clinic - Farhana Ikmal Hisham; Yasmine Choroomi; Melissa Chen; Meredith Fils (Journal of Student-Run Clinics, 2024)
Introduction: The Interprofessional Community Clinic (ICC), a student-run free clinic (SRFC), utilized telemedicine during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. Doxy.me was utilized early in 2021 before switching to Zoom midway through the year. This study compares two metrics between the platforms: average duration of visits and the number of times patients lost connection.Methods: Visit lengths were extracted from the ICC’s clinic manager whiteboard. De-identified Athenahealth chat logs were analyzed for instances of patient loss of connection. Independent samples t-tests were conducted to analyze the differences in these variables between Doxy.me and Zoom.Results: Twenty-nine visits were conducted through Doxy.me, eight without an interpreter and 21 with a Spanish interpreter. Forty-three visits were conducted through Zoom, 17 without an interpreter and 26 with a Spanish interpreter. The average visit duration was 79.4 minutes for Doxy.me and 73.3 minutes for Zoom (p=0.218). The average visit duration without interpreters was 78.2 minutes for Doxy.me and 73.2 minutes for Zoom (p=0.615). The average visit duration with an interpreter was 79.8 minutes for Doxy.me and 73.3 minutes for Zoom (p= 0.262). There were 15 instances of connection loss with Doxy.me and two for Zoom (p=<0.001).Conclusions: There was no statistically significant difference in average patient visit duration, even when stratified by interpreter usage. Connection loss between the platforms was statistically significant, and this was utilized as a proxy for platform stability. This difference could be attributed to the large participant volume per call. Additionally, patients often utilize mobile devices for visits, which could cause instability as Doxy.me could not run in the background upon switching apps. The ICC continues to utilize Zoom for telehealth visits due to the benefits with cost, stability, and promotion of interprofessionalism.